2018
DOI: 10.1007/s10955-018-2013-1
|View full text |Cite
|
Sign up to set email alerts
|

Genealogical Properties of Subsamples in Highly Fecund Populations

Abstract: We consider some genealogical properties of nested samples. The complete sample is assumed to have been drawn from a natural population characterised by high fecundity and sweepstakes reproduction (abbreviated HFSR). The random gene genealogies of the samples are -due to our assumption of HFSR -modelled by coalescent processes which admit multiple mergers of ancestral lineages looking back in time. Among the genealogical properties we consider are the probability that the most recent common ancestor is shared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Taking for some , Eldon and Wakeley (2006) obtain Λ-coalescents for which the Λ measure in Equation (2) is a point mass at ψ . The simplicity of this model does allow one to obtain some explicit mathematical results (see e.g ., Der et al 2012 ; Eldon and Freund 2018 ; Freund 2020 ; Matuszewski et al 2018 ), and the model has also been used to simulate gene genealogies within phylogenies ( Zhu et al 2015 ). As well as the haploid model of Eldon and Wakeley (2006) , provides the diploid version of Birkner et al (2013a ), in which individuals perish as above, but replacements are generated by sampling a single pair of diploid individuals as parents, with children sampling one chromosome from each parent.…”
Section: Mutation Generationmentioning
confidence: 99%
“…Taking for some , Eldon and Wakeley (2006) obtain Λ-coalescents for which the Λ measure in Equation (2) is a point mass at ψ . The simplicity of this model does allow one to obtain some explicit mathematical results (see e.g ., Der et al 2012 ; Eldon and Freund 2018 ; Freund 2020 ; Matuszewski et al 2018 ), and the model has also been used to simulate gene genealogies within phylogenies ( Zhu et al 2015 ). As well as the haploid model of Eldon and Wakeley (2006) , provides the diploid version of Birkner et al (2013a ), in which individuals perish as above, but replacements are generated by sampling a single pair of diploid individuals as parents, with children sampling one chromosome from each parent.…”
Section: Mutation Generationmentioning
confidence: 99%
“…Viewing time in units of scriptO)(Nγ generations for some γ](0,2, it can be shown that the model is in the domain of attraction of a normalΛ‐coalescent, indeed for γ=2 the limiting coalescent is a mixture of the Kingman‐coalescent and a multiple‐merger coalescent (Eldon & Wakeley, 2006). The model in Equation () is unrealistic in assuming that exactly the same fraction )(ψ of the population is replaced in each sweepstakes event, but it is among the simplest models of random sweepstakes, and its simplicity does facilitate some mathematical results to be obtained (Der et al, 2012; Eldon & Freund, 2018; Matuszewski et al, 2018). In particular, fixation probabilities under selection are studied for generalized Wright‐Fisher processes (Der et al, 2011).…”
Section: The Impact Of Random Sweepstakes On Selectionmentioning
confidence: 99%
“…The simplicity of this model does allow one to obtain some explicit mathematical results (see e.g. Der et al (2012); Eldon and Freund (2018); Freund (2020); Matuszewski et al (2018)), and the model has also been used to simulate gene genealogies within phylogenies . As well as the haploid model of Eldon and Wakeley (2006), msprime provides the diploid version of Birkner et al (2013a), in which individuals perish as above, but replacements are generated by sampling a single pair of diploid individuals as parents, with children sampling one chromosome from each parent.…”
Section: Availabilitymentioning
confidence: 99%